2018
DOI: 10.18632/oncotarget.25628
|View full text |Cite
|
Sign up to set email alerts
|

Marek’s disease virus oncoprotein Meq physically interacts with the chicken infectious anemia virus-encoded apoptotic protein apoptin

Abstract: Marek's disease (MD) is a neoplastic disease of poultry caused by Marek's disease virus (MDV), a highly contagious alphaherpesvirus. Meq, the major MDV oncoprotein, induces neoplastic transformation of T-cells through several mechanisms, including inhibition of apoptosis. In contrast, the chicken anemia virus (CAV)-encoded protein apoptin (VP3) is a powerful inducer of apoptosis of tumor cells, a property that is exploited for anticancer therapeutics. Although the molecular mechanisms of selective induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Although HVT genome organization shows extensive similarity with the MDV genome, HVT is the only avian alphaherpesvirus, which encodes a Bcl-2 homolog, vNr-13, expressed from two identical copies from the gene HVT079 and HVT096 (9,34). Several MDV and ILTV proteins were shown to have anti-apoptotic properties but none of them have Bcl-2 homology (27,45,46). Multiple sequence alignments revealed that vNr-13 shared the highest sequence identity of 64.4% with chicken Nr-13, compared to only 30% with the frog homolog (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although HVT genome organization shows extensive similarity with the MDV genome, HVT is the only avian alphaherpesvirus, which encodes a Bcl-2 homolog, vNr-13, expressed from two identical copies from the gene HVT079 and HVT096 (9,34). Several MDV and ILTV proteins were shown to have anti-apoptotic properties but none of them have Bcl-2 homology (27,45,46). Multiple sequence alignments revealed that vNr-13 shared the highest sequence identity of 64.4% with chicken Nr-13, compared to only 30% with the frog homolog (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, total RNA extracted from HVTinfected CEF using RNeasy mini kit (QIAGEN, Crawley, UK) was reverse transcribed using Superscript III (Invitrogen) kit according to manufacturer's instructions. After denaturation of the reverse transcriptase at 70 °C for 15 min, 5 µl of the reaction was used in a 50 µl volume polymerase chain reaction (PCR) containing 10 mM dNTP, 10 µM of each primer (Table 1) (27). Plasmid pX330A-1x2 was used for cloning of guide RNAs (gRNAs) for CRISPR/Cas9-based gene editing (see below).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Brown et al [61] reported for the first time that the meq protein can physically, and potentially functionally, interact with the chicken anemia virus (CAV) apoptin protein transactivating the CAV transcription [62]. CAV is an economically important immunosuppressive virus of chickens that causes anemia, lymphoid atrophy, morbidity, and mortality and synergizes with many co-infecting pathogens, including MDV, as demonstrated for avian respiratory viruses [22].…”
Section: The Oncogene Carried By MDVmentioning
confidence: 99%
“…MEQ also assists in MDV-associated oncogenesis by inhibiting the apoptosis of infected cells [ 134 , 149 , 150 ]. For example, MEQ binds and inhibits the apoptosis inducer apoptin in DF-1 cells [ 149 ].…”
Section: Meq: the Marek’s Disease Virus (Mdv) Bzip Transcription Fmentioning
confidence: 99%